Analisis Pelaksanaan Perkawinan Beda Agama di Indonesia Serta Problematika Hukum Pengakuan, Pencatatan, dan Pertanggungjawaban Pidana Pemalsuan Data Administrasi - Mochammad Verdan Dafa Maulana; Tomy Michael (Media Hukum Indonesia (MHI), 2026)
Interfaith marriage in Indonesia remains a legal issue that continues to generate debate due to the intersection between state law and religious law. The legal validity of marriage, as stipulated in Article 2 paragraph (1) of Law Number 1 of 1974 on Marriage, as amended by Law Number 16 of 2019, requires that a marriage be conducted in accordance with the laws of the respective religions and beliefs of the parties involved. In practice, this provision has given rise to various legal issues, particularly regarding the recognition and registration of interfaith marriages. This study aims to analyze the legal framework governing the implementation of interfaith marriages in Indonesia, as well as the legal challenges concerning their recognition and registration. The research employs a normative legal research method using statutory and case approaches. The legal materials consist of primary, secondary, and tertiary legal sources, which are analyzed using a descriptive qualitative method. The findings indicate that Indonesian positive law does not provide explicit regulations governing interfaith marriages, resulting in legal uncertainty. The legal issues identified include differing interpretations of statutory provisions, inconsistencies in judicial decisions, and obstacles in the marriage registration process. The issuance of Supreme Court Circular Letter (SEMA) Number 2 of 2023 serves as guidance for judges in promoting consistency in the application of the law in cases concerning interfaith marriage.